Civilization Past and Present - WALLBANK, T. Walter (Scott , Foresman and Comp, 1956)
The authors of the Eleventh Edition of "Civilization Past and Present" specialists in Islamic, African, Asian, Ancient, Russian, and East European history weave the diverse trends of world history into a clear and accessible analysis for today's students. "Civilization Past and Present," well known in the marketplace as a highly readable survey text, delivers a strong narrative of world history and a level of detail that is manageable for students and solid for instructors. Using images and documents that enhance the text's content, the narrative traces connections across cultures and introduces intriguing avenues of historical interpretation. The text examines all aspects of world history social, political, economic, religious, cultural, and geographic